An Economic Analysis on Automated Construction Safety Internet of Things, Artificial Intelligence and 3D Printing - Li, Rita Yi Man (Springer Singapore, 2018)
This book addresses information technologies recently applied in the field of construction safety. Combining case studies, literature reviews and interviews to study the issue, it presents cutting-edge applications of various information technologies (ITs) in construction in different parts of the world, together with a wealth of figures, tables and examples. Though primarily intended for researchers and experts in the field, the book will also benefit graduate students.